دراسة امكانية استعمال مستخلص المائي للوردة العربي كمبيدو كمغذي نباتي - عقيب رجاء (جامعة الوادي - university of eloued, 2024)
This study aims to test the possibility of using the aqueous extract of Rose Arabia as a plant nutrient and as an insect repellent, as it was studied in the state of Oued Souf in Algeria. Rose water was tested as a plant nutrient and applied to pumpkin seeds at different concentrations. The results showed clear significant differences with pumpkin seeds in terms of germination and growth. I also studied the aqueous extract of the Arabian rose, as it was applied as a pesticide against insects, aphids in oleander and vine plants, and pea larvae, where good results were recorded with both pea larvae and aphids, where the moment the aphids swelled and the color changed from yellow to brown, and the aphids had The green color also turns to brown. As for the pea larvae, they stop eating and then swell and change color from green to brown. The brown larvae turn to black, then die, as the rate of insect death was significant, and from the results obtained, the use of the extract The water content of the Arabian rose had a toxic effect on aphids in the vineyard, as the moment the concentration increased, the death rate increased over time, as the death rate of aphids reached a maximum of 95% . The studies we conducted also showed that the aqueous extract of the Arabian rose has no effect on the plant, that is, there is no negative effect on the plant. From this research it is clear that the aqueous extract of the Arabian rose is effective in killing Aphis insects and larvae in peas, as it is a means of biological control that is safe for the environment and does not affect the environmental balance. There are alternatives. Chemical pesticides with harmful effects.
انتاج نباتي
Keywords: Arabian Rose Extract; Aphids; Pea Caterpillars; Plant Nutrient; Biologically Controlled.